2005
DOI: 10.1016/s0002-9440(10)62330-9
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Fas/FasL Apoptotic Pathway in Ulcer Formation during Leishmania major-Induced Cutaneous Leishmaniasis

Abstract: Cutaneous leishmaniasis (CL), caused by the intracellular protozoan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 43 publications
3
40
0
1
Order By: Relevance
“…79 En las lesiones de pacientes con LC infectados con L. major se detectó sobreexpresión de FasL en macrófagos y linfocitos T activados, en nexo con expresión de Fas; empero, se vinculó con la formación de la úlcera, ya que se encontró un buen número de queratinocitos en apoptosis. 80 También se ha informado una correlación entre la citotoxicidad in vitro de linfocitos de sangre periférica de pacientes con LC contra macrófagos infectados con L. major y la liberación de granzima B. 72 Toda la evidencia señala la participación de la citotoxicidad en la reacción inmunitaria específica y parece relacionarse con la curación.…”
Section: Degradación De Leishmaniaunclassified
“…79 En las lesiones de pacientes con LC infectados con L. major se detectó sobreexpresión de FasL en macrófagos y linfocitos T activados, en nexo con expresión de Fas; empero, se vinculó con la formación de la úlcera, ya que se encontró un buen número de queratinocitos en apoptosis. 80 También se ha informado una correlación entre la citotoxicidad in vitro de linfocitos de sangre periférica de pacientes con LC contra macrófagos infectados con L. major y la liberación de granzima B. 72 Toda la evidencia señala la participación de la citotoxicidad en la reacción inmunitaria específica y parece relacionarse con la curación.…”
Section: Degradación De Leishmaniaunclassified
“…1 However, some of the results obtained in this context indicated that Fas pathway may not be the only player involved in apoptosis of keratinocytes during CL. For example, when soluble FasL (sFasL)-containing supernatants from restimulated CL peripheral blood mononuclear cells (PBMCs) were used to induce apoptosis in human keratinocytes, blocking of the Fas/ FasL pathway inhibited apoptosis only in two thirds of the analyzed supernatants.…”
mentioning
confidence: 92%
“…At the site of the ulcer, in the dermis of the skin, L. majorinfected macrophages and infiltrating, activated T cells, monocytes, neutrophils, and plasma cells are found. We 1 and others 2,3 have suggested a role for Fas apoptosis mediated by its natural ligand (FasL) in ulcer formation and parasite clearance during CL.…”
mentioning
confidence: 96%
“…In addition, increased Fas/FasL expression was detected in cells infiltrating cutaneous lesions in murine infection [21]. Moreover, systemic neutralization of FasL and TRAIL reduces skin ulceration in experimental Leishmaniasis [22].…”
Section: Introductionmentioning
confidence: 98%